2016
DOI: 10.1093/jnen/nlw070
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Load of Amyloid-β Pathology in Parkinson Disease and Dementia with Lewy Bodies

Abstract: Parkinson disease (PD), Parkinson disease with dementia (PDD), and Dementia with Lewy bodies (DLB) differ clinically with regard to the presence and timing of dementia. In this postmortem study, we evaluated whether the burden and distribution pattern of amyloid-β (Aβ) pathology differs among these disease entities. We assessed Aβ phases and neuritic plaque scores in 133 patients fulfilling clinical diagnostic criteria for PD, PDD, and DLB, and determined the presence and load of Aβ pathology in 5 cortical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 58 publications
7
98
0
Order By: Relevance
“…Of note 28% of DLB and 10% PDD cases had sufficient pathology for a secondary neuropathological diagnosis of AD. This has been consistently demonstrated in multiple studies, as Ab plaques are reportedly observed more in the entorhinal cortex, amygdala and putamen (Hepp et al 2016), in addition to Ab burden being significantly higher in cortical and subcortical regions in DLB compared to PDD (Jellinger and Attems 2006;Edison et al 2008;Halliday et al 2011;Walker et al 2015;Hepp et al 2016).…”
Section: Neuropathological Considerationssupporting
confidence: 67%
See 1 more Smart Citation
“…Of note 28% of DLB and 10% PDD cases had sufficient pathology for a secondary neuropathological diagnosis of AD. This has been consistently demonstrated in multiple studies, as Ab plaques are reportedly observed more in the entorhinal cortex, amygdala and putamen (Hepp et al 2016), in addition to Ab burden being significantly higher in cortical and subcortical regions in DLB compared to PDD (Jellinger and Attems 2006;Edison et al 2008;Halliday et al 2011;Walker et al 2015;Hepp et al 2016).…”
Section: Neuropathological Considerationssupporting
confidence: 67%
“…This has been consistently demonstrated in multiple studies, as Aβ plaques are reportedly observed more in the entorhinal cortex, amygdala and putamen (Hepp et al . ), in addition to Aβ burden being significantly higher in cortical and subcortical regions in DLB compared to PDD (Jellinger and Attems ; Edison et al . ; Halliday et al .…”
Section: Neuropathological Considerationsmentioning
confidence: 99%
“…The accumulation of LBs in LB-related disorders is not sufficient to explain the developing of dementia in all the cases, since some PD patients with a high neocortical LB burden remain cognitively intact [56]. Co-occurrence of β-amyloid plaques and LBs is associated with a higher cognitive impairment [57] and it is a better predictor of dementia compared with the accumulation of LBs or β-amyloid alone [56]; DLB patients who show the presence of β-amyloid deposition tend to develop a higher rate of brain atrophy with an AD-like pattern[57]; moreover a recent study reported that increasing severity of AD neuropathology in patients with LB-related diseases may lead to a narrower interval between the onset of motor symptoms and the development of dementia [58]. In light of these findings we explored our cohort and among the 32 patients with β-amyloid in the brain autopsy, 18 (56.3%) were clinically diagnosed as demented.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, DLB and PDD cases were grouped together as one Lewy body dementia cohort to investigate effects of antidepressant treatment on neurogenesis and cognition. Whilst the 1-year rule is still routinely clinically applied to differentiate between the two dementia forms, several studies have suggested differences in amyloid load and Lewy body cortical load [47,48,49,50,51] which could also have an impact on the rate of neurogenesis. It would, therefore, be of interest to take this into consideration in future studies investigating neurogenesis in DLB/PDD.…”
Section: Discussionmentioning
confidence: 99%